Wi-fi analyzer for users to optimize current network - Tay, Boon Yan (2023)
This project is a mobile application development for Wi-Fi analyze purpose. It is an Android application which displays the parameters of the connected Wi-Fi network. The parameters include Service Set Identifier (SSID), Strength, Signal Level, Signal Strength, Speed, Internet Protocol (IP) Address, Media Access Control (MAC) Address and Frequency. The main objective is to analyze the connection, collect the data, and diagnose the issues that are causing a poor Wi-Fi signal. The impact of this project is that when the Wi-Fi network come with some issues related to network implementation, security, and maintenance. For example, the location of your router, the channel you choose for data transmission, and the capacity of the signal to reach all intended users can all have a significant impact on the flexibility and usefulness of your Wi-Fi network. The usage of tools like a Wi-Fi signal analyzer can be quite helpful for maintaining the Wi-Fi network's top performance. The emphasis of this project is laid on collecting the data from network's various access points and channels and present it in a comprehensible manner via visual reports and dashboards. The development tool used in this project is the Android Studio and Java.